Investments - Bodie, Zvi; Kane, Alex; Marcus, Alan (Boston: McGraw-Hill, 2008)
This a textbook on investment analysis. The central theme fo the text is the near efficiency of a well developed security markets; the risk-return trade-off.
Includes bibliographical reference and index.
lje 12/9/13
Loans
Keywords: Investments